2017
DOI: 10.3847/1538-4357/aa7da2
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Cloud S242: Physical Environment and Star-formation Activities

Abstract: We present a multi-wavelength study to probe the star formation (SF) processes on a larger scale (∼1• .05 × 0 • .56) around the S242 site. The S242 molecular cloud is depicted in a velocity range from −3.25 to 4.55 km s −1 and has spatially elongated appearance. Based on the virial analysis, the cloud is prone to gravitational collapse. The cloud harbors an elongated filamentary structure (EFS; length ∼25 pc) evident in the Herschel column density map and the EFS has an observed mass per unit length of ∼200 M … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 65 publications
4
44
2
1
Order By: Relevance
“…Recently, Kainulainen et al (2016) found the fragmentation strongly at the ends of the Musca cloud. Dewangan et al (2017) also found massive clumps and YSO clusters prefer to locate at the both ends of the filamentary molecular cloud S242. These authors suggest the so-called end-dominated collapse may be responsible.…”
Section: Star Formation Scenariomentioning
confidence: 79%
See 1 more Smart Citation
“…Recently, Kainulainen et al (2016) found the fragmentation strongly at the ends of the Musca cloud. Dewangan et al (2017) also found massive clumps and YSO clusters prefer to locate at the both ends of the filamentary molecular cloud S242. These authors suggest the so-called end-dominated collapse may be responsible.…”
Section: Star Formation Scenariomentioning
confidence: 79%
“…Based on farinfrared and/or millimeter sky surveys such as Herschel InfraRed Galactic Plane Survey (Hi-GAL; Molinari et al 2010) and Atacama Pathfinder Experiment Telescope Large Area Survey of the Galaxy (ATLASGAL; (Schuller et al 2009), it is demonstrated that filamentary structures are ubiquitous in the ISM and play an important role in the processes of star formation. They could fragment into clumps because of gravitational instabilities (e.g., André et al 2010;Ragan et al 2014;Li et al 2016;Dewangan et al 2017, and references therein). However, the nature of filamentary structures is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…From the distribution of young stellar candidates, the spatial extent of the elongated structure is estimated as ∼ 43 (26 pc). Using the 13 CO molecular line data, Dewangan et al (2017) also reported the presence of an EFS of length ∼ 25 pc and average width ∼ 1.3 pc. A significant number of the Class I sources have formed two discrete groups, one at the central region and another at the northern end of the long scale structure.…”
Section: Spatial Distribution Of the Pms Populationmentioning
confidence: 94%
“…O. L. Ryabukhina 1,2 , L. E. Pirogov 2 1 Institute of Astronomy RAS, 2 Institute of Applied Physics RAS An elongated gas-dust filament is associated with the massive starforming region S242. According to our 13 CO(1-0) observations, the length of the filament is more than 30 pc.…”
Section: Study Of the Filamentary Dark Cloud In The S242 Regionmentioning
confidence: 99%
“…Исследуемая волокнообразная область S242 вытянута более чем на 30 пк. Вблизи краев волокна обнаружены скопления внутренних молодых звездных объектов, указывающие на активный процесс звездообразования [2].…”
Section: Study Of the Filamentary Dark Cloud In The S242 Regionunclassified